2014
DOI: 10.5483/bmbrep.2014.47.7.191
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulating activity of maysin isolated from corn silk in murine RAW 264.7 macrophages

Abstract: Corn silk (CS) has long been consumed as a traditional herb in Korea. Maysin is a major flavonoid of CS. The effects of maysin on macrophage activation were evaluated, using the murine macrophage RAW 264.7 cells. Maysin was isolated from CS by methanol extraction, and preparative C18 reverse phase column chromatography. Maysin was nontoxic up to 100 μg/ml, and dose-dependently increased TNF-α secretion and iNOS production by 11.2- and 4.2-fold, respectively, compared to untreated control. The activation and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…In addition, two polyphenol components of pomegranate extract (punicalagin and ellagic acid) ameliorated the cognitive impairment, which may counteract the microglia activation and accelerated inflammation associated with the Aβ-induced pro-inflammatory cytokine, TNF-α, in (APP/PS1) transgenic AD mice [52]. In accord with these data, one of the CG extract compounds, Maysin has shown insecticidal activity against corn earworm [53], anti-inflammatory effects by inducting the pro-inflammatory cytokine, TNF-α, and inducible nitric-oxide synthase (iNOS) gene expression coupled with the phosphorylation of Akt and MAPK signaling in activated macrophage [54]. Similar to these scientific findings, our results also indicate that the CG compound could induce the Th2 cytokine response as a result of the enhanced levels of the anti-inflammatory profile, as shown by IL-4 and IL-10- induction in the EA-CG (Maysin and its flavonoid derivatives)-treated Tg AD mice after six months of an EA-CG diet.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, two polyphenol components of pomegranate extract (punicalagin and ellagic acid) ameliorated the cognitive impairment, which may counteract the microglia activation and accelerated inflammation associated with the Aβ-induced pro-inflammatory cytokine, TNF-α, in (APP/PS1) transgenic AD mice [52]. In accord with these data, one of the CG extract compounds, Maysin has shown insecticidal activity against corn earworm [53], anti-inflammatory effects by inducting the pro-inflammatory cytokine, TNF-α, and inducible nitric-oxide synthase (iNOS) gene expression coupled with the phosphorylation of Akt and MAPK signaling in activated macrophage [54]. Similar to these scientific findings, our results also indicate that the CG compound could induce the Th2 cytokine response as a result of the enhanced levels of the anti-inflammatory profile, as shown by IL-4 and IL-10- induction in the EA-CG (Maysin and its flavonoid derivatives)-treated Tg AD mice after six months of an EA-CG diet.…”
Section: Discussionmentioning
confidence: 98%
“…We concluded that the effects of GEN7G on macrophage functions depend on signaling via nuclear ERs, because (1) the enhancing activities of genistein, liquiritigenin, and hesperetin on macrophage phagocytosis were correlated to the binding activities to nuclear ERs [17]; (2) the action of GEN7G was decreased by ICI-182780, which works as an antagonist of nuclear ERs and also as an agonist of membrane GPERs [19]; (3) estradiol enhanced macrophage phagocytosis at similar concentrations as genistein and GEN7G; (4) GEN7G showed no agonistic activity toward GPR30 even at the high concentration of 100 mmol/L, and genistein reduced intracellular signals following b-arrestin recruitment, although some papers have demonstrated the agonism of genistein [20,21]; and (5) some flavonoids known as phytoestrogens enhance the phagocytic activity of myeloid leukemia cells and activate macrophage-like cells [22][23][24][25][26][27]. Quantitative real-time PCR revealed that RAW264.7 cells dominantly expressed Esr1/ ERa, but not Esr2/ERb (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its methanolic extract has been found to be effective in thyroid dysfunction [47]. Corn silk extracts contain certain bioactive compounds which show immunomodulation activity [33,48,49]. Corn silk extracts have been also found to be effective in inhibition of tumor necrosis factor-α and adhesion of leukocytes to cell surface and induction of nitric oxide synthase and cyclooxygenase in macrophages [50][51][52].…”
Section: Corn Leavesmentioning
confidence: 99%